A co-crystallization induced surface modification strategy with cyanuric acid modulates the bandgap emission of carbon dots. Issue 20 (18th May 2020) - Zhou, Zhengjie; Ushakova, Elena V.; Liu, Enshan; Bao, Xin; Li, Di; Zhou, Ding; Tan, Zhanao; Qu, Songnan; Rogach, Andrey L.
Abstract : A co-crystallization strategy with cyanuric acid to modulate the bandgap emissions of CDs was realized to produce highly emissive solid composite CD-based materials. Abstract : Along the line of offering surface modification strategies to tune emission properties of carbon dots (CDs), a co-crystallization strategy with cyanuric acid (CA) was developed to modulate the bandgap emissions of CDs and produce highly emissive solid composite CD-based materials. The original blue emission of the CDs changed to a green emission of the CDs@CA crystals, which showed a high photoluminescence quantum yield of 62% and room temperature phosphorescence. The CA molecules firmly bonded to the surface of the CDs and cannot be disrupted by polar solvents or temperature stimuli under ambient conditions, which influenced electron transitions of CDs leading to improved luminescence with excellent thermal stability both in solution and solid states.